The water-energy-food nexus in Kazakhstan: challenges and opportunities - Karatayev, Marat; Rivotti, Pedro; Sobral Mourão, Zenaida; Konadu, D. Denis; Shah, Nilay; Clarke, Michèle (Elsevier, 2017)
The concept of the water, energy, food nexus is extremely relevant to Kazakhstan as the country faces population growth, economic progress and environmental challenges such as water scarcity, desertification, and climate change. Furthermore, poor sectoral coordination and inadequate infrastructure have caused unsustainable resource use and threaten the long-term water, energy and food security in Kazakhstan. This study presents the key elements required to implement a nexus-based resource management approach in Kazakhstan, by identifying linkages between water resources, energy production and agriculture. A case study illustrates how this methodology can be applied to quantify linkages between the water and energy sectors.